(5t+7)-(2t+7)=

Simple and best practice solution for (5t+7)-(2t+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5t+7)-(2t+7)= equation:


Simplifying
(5t + 7) + -1(2t + 7) = 0

Reorder the terms:
(7 + 5t) + -1(2t + 7) = 0

Remove parenthesis around (7 + 5t)
7 + 5t + -1(2t + 7) = 0

Reorder the terms:
7 + 5t + -1(7 + 2t) = 0
7 + 5t + (7 * -1 + 2t * -1) = 0
7 + 5t + (-7 + -2t) = 0

Reorder the terms:
7 + -7 + 5t + -2t = 0

Combine like terms: 7 + -7 = 0
0 + 5t + -2t = 0
5t + -2t = 0

Combine like terms: 5t + -2t = 3t
3t = 0

Solving
3t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '3'.
t = 0

Simplifying
t = 0

See similar equations:

| 12/(x^2+x-2)-(x+3)/(x-1)=(1-x)/(x+2) | | -3=-.5(n-6) | | -(1+7x)-6(-7x-x)=36 | | -5v-6(3v+2)=-150 | | 6v^2+13-28=0 | | 1/6(x+3)=1/9(8-x) | | -6y+17=3y-0 | | (2-x)/(x+2)+3=4/(x+2) | | 4x+(9-6(2x+3))-10= | | 15+w/9=-10 | | 6y^2+13y+15=0 | | 1/3x*(-18) | | 3z(z+6)=3z+18z-4 | | -5(8-4r)=-200 | | 0.2x+4.4=0.1x+3.1 | | 4/9w=88 | | -2(12a-8)=-5(a+8)-5a | | -140=4(6x+7) | | 4(3+8m)=12+8m | | 18x+3(4x-9)=-6x+81 | | 3X+9Y=-18 | | x-3/8-1=x-7/9 | | 8=11p+13 | | 9x^2+23x+4=0 | | -4(p+2)+8=2p(p-1)-7p+15 | | -104=8(p-8) | | 2.3(5-x)=-0.7(1-x) | | -2.05x+1.8(x-3)=6.2 | | -10p-3=-1+2(3p-9) | | X+x+42=180 | | 4x+72-4x=27x-21-4x | | 3x-13=8x+22 |

Equations solver categories